2022
DOI: 10.3390/ijerph192316164
|View full text |Cite
|
Sign up to set email alerts
|

Examining Learning Experience and Satisfaction of Accounting Students in Higher Education before and amid COVID-19

Abstract: The widespread outbreak of the COVID-19 virus had substantial impacts on higher education, which turned into distance using virtual environments and electronic (e) learning platforms. There is a growing body of research on the effect of COVID-19 on students’ education and e-learning experiences amid the pandemic. However, limited research was performed to assess the learning experience before and amid the COVID-19 pandemic among students in specific disciplines such as accounting. The current research compares… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
2
0
4
Order By: Relevance
“…Learning accounting subjects requires building complex memory patterns known as schemas (Abeysekera & Jebeile, 2019;Blaney et al, 2016) [11,12]. Previous research conducted at a university in the Middle East has shown that accounting students are better supported by participation and collaboration in traditional learning than in online learning environments (Shabeeb et al, 2022) [13]. The study findings differ due to national societal and cultural settings and how online learning was designed and implemented.…”
Section: Introductionmentioning
confidence: 85%
“…Learning accounting subjects requires building complex memory patterns known as schemas (Abeysekera & Jebeile, 2019;Blaney et al, 2016) [11,12]. Previous research conducted at a university in the Middle East has shown that accounting students are better supported by participation and collaboration in traditional learning than in online learning environments (Shabeeb et al, 2022) [13]. The study findings differ due to national societal and cultural settings and how online learning was designed and implemented.…”
Section: Introductionmentioning
confidence: 85%
“…De igual manera, en momentos posteriores y hasta la actualidad se siguen llevando a cabo estudios para conocer cuál ha sido el impacto de esto en estudiantes de diferentes etapas educativas (Adam, y Metljak, 2021), cómo han afectado dependiendo de la materia a los estudiantes (Nodeh, 2021) y a los docentes (Baykal, y TUTUNCU, 2022;Magarò, et al, 2023), cómo los diferentes elementos que se implementaron en el proceso de E-A durante ese periodo han perdurado o cómo todos los cambios han afectado a nivel emocional a los miembros de la comunidad educativa (Lin, et al, 2022;Shabeeb, et al, 2022).…”
Section: Experiencias Adquiridas Por Docentes Y Estudiantes En Este C...unclassified
“…Las plataformas de gestión del aprendizaje permiten a los estudiantes acceder a materiales de curso, participar en discusiones en línea y realizar actividades de evaluación. Las simulaciones contables ofrecen entornos virtuales donde los estudiantes pueden aplicar sus conocimientos en situaciones prácticas y reales, mientras que las videoconferencias facilitan la interacción en tiempo real con profesores y compañeros, creando un sentido de comunidad en línea (Navarro, 2020;Bordón & Britos, 2022;Prieto-Ballester et al, 2021;Shabeeb et al, 2022;Tamay-Chimborazo et al, 2020).…”
Section: Lasunclassified
“…Nota: Elaborado por el autor Se observa una clara migración hacia métodos de enseñanza en línea, con un aumento significativo en la adopción de tecnologías educativas. Estos cambios han llevado consigo una serie de desafíos, desde la autenticidad de las evaluaciones en línea hasta la necesidad de abordar los aspectos psicosociales del aprendizaje virtual (Corredor et al, 2022;Shabeeb et al, 2022).…”
Section: Alshurafat Et Al (2021)unclassified
See 1 more Smart Citation